The agricultural work of the Perm Zemstvo under regime of A. V. Kolchak - V. I. Teterin (Омский научный вестник: Серия "Общество. История. Современность")
The article describes the work of the Perm Zemstvo in the field of agricultural issues in the first half of 1919. The aim of the research is the study of the activities of agricultural departments under the district Council in terms of establishing a regime of A. V. Kolchak. In the front line in the conditions of the Civil war, agricultural problems acquired special importance, so the government paid great attention to the agricultural departments of the Zemstvo. The author analyzes the activities of the Zemstvo in the field of agriculture, which covered a wide range of tasks from the selection of qualified agricultural personnel to the institutionalization of agricultural education. The author draws conclusions about the place of agricultural departments in the policy of A. V. Kolchak